Foaming material not prone to dust falling and water absorption and preparation method of foaming material

By optimizing the formulation and molding process of foaming materials, combined with modified polysiloxane, waterproof modifier and adhesion promoter, the problem of existing foaming materials being difficult to adhere while maintaining hydrophobicity and dustproof performance is solved, and efficient adhesion and high-performance foaming materials are achieved.

CN119591963APending Publication Date: 2025-03-11DONGGUAN ZHAOYANG XINGYE PLASTIC PROD CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411993903.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

While existing foaming materials maintain good hydrophobicity and dustproof properties, it is difficult to achieve effective adhesion to other materials or coatings.

Method used

The formula consisting of olefin polymers, modified polysiloxanes, waterproof modifiers, antioxidants, surfactants, plasticizers, foaming agents, fillers, stabilizers and adhesion promoters is prepared through specific mixing and molding processes.

Benefits of technology

The hydrophobicity and dust-proof properties of foamed materials are significantly improved, while enhancing their adhesion to other materials or coatings, achieving good bonding effect without additional surface treatment, simplifying production processes and reducing production costs.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention belongs to the technical field of foaming materials, and particularly relates to a foaming material not prone to dust falling and water absorption and a preparation method of the foaming material. The material consists of the following components in parts by weight: 30-50 parts of an olefin polymer, 2-8 parts of modified polysiloxane, 1-5 parts of a waterproof modifier, 0.5-2 parts of an antioxidant, 0.5-3 parts of a surfactant, 2-10 parts of a plasticizer, 3-7 parts of a foaming agent, 10-30 parts of a filler, 1-4 parts of a stabilizer and 1-6 parts of an adhesion promoter. By optimizing the formula design and particularly introducing the modified polysiloxane, the waterproof modifier and the adhesion promoter, the hydrophobic property and the dustproof property of the material are enhanced, the adhesion between the material and other materials or coatings is also remarkably improved, and a good adhesion effect can be obtained without additional surface treatment steps. According to the technical scheme, the production process is simplified, the production cost is reduced, and meanwhile the high performance of the material is guaranteed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of foaming materials, and particularly relates to a foaming material which is not easy to shed dust or absorb water and a preparation method thereof. Background Art

[0002] In modern materials science, foam materials are widely used in packaging, construction, automotive interiors and other fields due to their excellent properties such as light weight, heat insulation, sound insulation and cushioning. Traditional foam materials are usually composed of a polymer matrix and an appropriate foaming agent, and are made through a specific processing technology. However, existing foam materials often have some shortcomings, especially in terms of hydrophobicity and dustproof performance. Although some foam materials have certain waterproof capabilities, they are prone to adsorb dust and have difficulties in bonding with other materials or coatings.

[0003] Most of the foaming materials in the prior art use a single type of polymer as the matrix, such as polyethylene (PE), polypropylene (PP), etc., and add a small amount of functional additives to improve its physical properties. In order to achieve the hydrophobic effect, a simple fluoride water repellent is usually used, but these treatments may not completely prevent water penetration, especially after long-term exposure to humid environments. In addition, since the surface energy of the foaming material is low, although this helps to reduce dust adhesion, it also leads to the problem of insufficient adhesion between other materials or coatings. Summary of the invention

[0004] The purpose of the present invention is to provide a foam material that is not easy to collect dust and absorb water and a preparation method thereof, which not only enhances the hydrophobicity and dustproof properties of the material, but also significantly improves its adhesion with other materials or coatings, so as to solve the technical problem that the existing foam material is difficult to achieve effective adhesion with other materials or coatings while maintaining good hydrophobicity and dustproof properties.

[0005] To achieve the above object, the present invention provides a foaming material that is not easy to fall dust and is not easy to absorb water. The foaming material is composed of the following formula components in parts by weight, including: 30-50 parts of olefin polymer; 2-8 parts of modified polysiloxane; 1-5 parts of waterproof modifier; 0.5-2 parts of antioxidant; Surfactant 0.5-3 parts; 2-10 parts of plasticizer; 3-7 parts of foaming agent; 10-30 parts of filler; 1-4 parts of stabilizer; Adhesion promoter 1-6 parts.

[0006] Preferably, the olefin polymer is selected from one or more combinations of low-density polyethylene, linear low-density polyethylene, and high-density polyethylene.

[0007] Preferably, the modified polysiloxane is polydimethylsiloxane modified with amino, epoxy or other functional groups.

[0008] Preferably, the waterproof modifier is a perfluoroalkylethanol modified with silk fibroin.

[0009] Preferably, the filler includes but is not limited to calcium carbonate, talc, and silicon dioxide.

[0010] Preferably, the adhesion promoter comprises a silane coupling agent or a titanate compound.

[0011] On the other hand, the present invention provides a method for preparing a foaming material that is not easy to fall dust and not easy to absorb water, comprising the following steps: 30-50 parts of olefin polymer, 2-8 parts of modified polysiloxane, 1-5 parts of waterproof modifier, 0.5-2 parts of antioxidant, 0.5-3 parts of surfactant, 2-10 parts of plasticizer, 1-4 parts of stabilizer and 1-6 parts of adhesion promoter are uniformly mixed to obtain mixture A; Adding 3-7 parts of a foaming agent to the mixture, and fully mixing the mixture under controlled temperature and pressure conditions to obtain a mixture B; Add 10-30 parts of filler to mixture B and continue stirring until all ingredients are completely blended to obtain mixture C; The mixture C is made into a foam material of a desired shape through extrusion, injection or compression molding, and the molded foam material is cooled, shaped, demolded and surface treated.

[0012] Preferably, the olefin polymer is preheated before mixing, and the preheating temperature ranges from 80 to 120°C.

[0013] Preferably, the molding process adopts compression molding, the molding temperature is 150-200° C., the molding pressure is 5-15 MPa, and the holding time is 3-10 minutes.

[0014] Preferably, the mixing is performed under controlled temperature and pressure conditions to obtain a mixture B, comprising: The temperature is controlled at 40-80°C and the mixing pressure is maintained at 0.5-2.0MPa; A high-speed stirring device is used with the stirring speed set at 800-1500 rpm and the stirring time set at 3-8 minutes to obtain a mixture B.

[0015] Technical effects and advantages of the present invention: The present invention provides a foaming material that is not easy to fall dust and absorb water. The material is composed of the following components in parts by weight: 30-50 parts of olefin polymer, 2-8 parts of modified polysiloxane, 1-5 parts of waterproof modifier, 0.5-2 parts of antioxidant, 0.5-3 parts of surfactant, 2-10 parts of plasticizer, 3-7 parts of foaming agent, 10-30 parts of filler, 1-4 parts of stabilizer, and 1-6 parts of adhesion promoter. By optimizing the formula design, especially introducing modified polysiloxane, waterproof modifier and adhesion promoter, the present invention not only enhances the hydrophobicity and dustproof performance of the material, but also significantly improves its adhesion with other materials or coatings, and a good bonding effect can be obtained without additional surface treatment steps. This technical solution simplifies the production process, reduces production costs, and ensures the high performance of the material. DETAILED DESCRIPTION

[0016] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. The specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0017] The olefin polymer of the present invention is selected from one or more combinations of low-density polyethylene, linear low-density polyethylene, and high-density polyethylene. As a matrix material, olefin polymers (such as polyethylene and polypropylene) provide basic physical properties of foaming materials, including good mechanical strength, flexibility and chemical resistance. They also have a lower density, which helps to make lightweight materials. They act as a skeleton in the formula, provide a carrier for other additives, and ensure the structural stability and processing performance of the final product.

[0018] The modified polysiloxane of the present invention is a polydimethylsiloxane modified by amino, epoxy or other functional groups. The modified polysiloxane can improve the surface properties and reduce the surface energy, thereby improving the hydrophobicity and dustproof performance. It can also enhance the adhesion with other materials or coatings. When used in combination with olefin polymers, it can give the material excellent surface characteristics and bonding properties while maintaining good mechanical properties.

[0019] The waterproof modifier of the present invention is a perfluoroalkylethanol modified by silk fibroin. The branches with positive and negative charges on the silk of silk fibroin attract water, but the silk fibroin covered with perfluorocarbon hardly adsorbs water together. The modified perfluoroalkylethanol greatly improves the waterproof performance of the material and prevents water penetration. It works synergistically with the modified polysiloxane to strengthen the waterproof barrier of the material, ensuring that the performance can be kept stable even after long-term exposure to a humid environment. The modification method of perfluoroalkylethanol is as follows: dissolve the silk fibroin in a PBS buffer solution, and use acetic acid to dropwise adjust the pH of the silk fibroin solution to 4.5, and fix the volume to a concentration of 8% (w / v) to obtain a silk fibroin solution, and then add 0.5 weight parts of polyethylene glycol diglycidyl ether and 0.5 weight parts of 1-ethyl-3-(3-methylaminopropyl) carbodiimide to 2 weight parts of the silk fibroin solution and stir, add 3 weight parts of the stirred solution to 10 weight parts of perfluoroalkylethanol, and continue to stir evenly to obtain a perfluoroalkylethanol modified by silk fibroin.

[0020] The antioxidant of the present invention protects the material from oxidative degradation, prolongs the service life, and maintains the color and appearance of the material. It improves the aging resistance of the entire system and ensures the consistency and reliability of the material under various environmental conditions; specifically includes: Hindered Phenols Ingredient examples: Irganox 1010 (pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate), Irganox 1076 (n-octadecylβ-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate); Hindered phenolic antioxidants are a widely used class of primary antioxidants that interrupt free radical chain reactions, thereby preventing thermo-oxidative degradation of polymers. These compounds have high thermal stability and are suitable for applications that require prolonged high temperature processing.

[0021] Phosphite antioxidants (Phosphites and Phosphonites): Ingredient examples: Irgafos168 (tris (2,4-di-tert-butylphenyl) phosphite), Weston619 (bis (2,4-dicumylphenyl) pentaerythritol diphosphite) Phosphite antioxidants are mainly used as auxiliary antioxidants. They can decompose peroxides and prevent the oxidation process caused by hydroperoxides. This type of antioxidant is usually used in conjunction with hindered phenol antioxidants to provide more comprehensive protection.

[0022] Thiodipropionates: Ingredient Example: Didodecylthiodipropionate (DSTDP) Antioxidants of this type inhibit oxidation reactions by capturing free radicals and are particularly useful in systems that are sensitive to metal-catalyzed oxidation. They can also act as halogen absorbers, reducing oxidation reactions that are accelerated by the presence of halogens.

[0023] In this embodiment, one or more antioxidant combinations of the above types are used to ensure optimal antioxidant performance. For example, a hindered phenol antioxidant (such as Irganox 1010) can be selected as the main antioxidant and combined with an appropriate amount of a phosphite antioxidant (such as Irgafos 168) to achieve an efficient synergistic effect. This combination can not only effectively prevent thermal oxidative degradation of the material during processing, but also extend the life of the finished product in actual use.

[0024] The surfactant of the present invention helps to promote the uniform dispersion of the ingredients during the mixing process, especially for the ingredients that are not easily miscible, such as plasticizers and waterproofing agents. It improves the processing fluidity, ensures the uniformity of the internal structure of the finished product, and reduces defects and unevenness. Specifically, it includes: Nonionic Surfactants: Ingredient examples: polyoxyethylene alkyl ethers (e.g. Brij35), polyoxyethylene sorbitan fatty acid esters (e.g. TWEEN series, such as TWEEN20, TWEEN80). Nonionic surfactants are widely used in polymer processing. They promote mixing between different phases by reducing interfacial tension and are particularly suitable for emulsification of oil-water two-phase systems. These surfactants have good thermal and chemical stability and do not react with most polymers.

[0025] Anionic Surfactants: Ingredient examples: alkylbenzene sulfonates (such as sodium dodecylbenzene sulfonate, SDBS), fatty acid soaps (such as sodium stearate). Anionic surfactants can provide strong detergency and foam formation, while helping to improve dispersibility. They can effectively stabilize suspensions and emulsions and have good compatibility with certain types of plasticizers and water-repellents.

[0026] Cationic Surfactants: Ingredient examples: quaternary ammonium salts (e.g., cetyltrimethylammonium bromide, CTAB); Cationic surfactants are often used to impart antimicrobial properties or to modify charge characteristics, but they can also be used as effective wetting and dispersing agents. These surfactants enhance adsorption to negatively charged surfaces, thereby improving adhesion and coating quality.

[0027] Amphoteric Surfactants: Ingredient example: Cocamidopropyl Betaine (CAPB); Amphoteric surfactants are able to remain active over a wide pH range and exhibit mild properties, making them suitable for applications that require low irritation. They can also work synergistically with other types of surfactants to optimize performance.

[0028] Silicone Surfactants: Ingredient example: Dimethicone copolyol (e.g. Dow Corning DC-57); Silicone surfactants are known for their excellent lubricity and hydrophobicity, which can significantly reduce surface tension and improve leveling. This type of additive is particularly suitable for applications that require high gloss and good feel.

[0029] For the foaming material formulation in this embodiment, one or more surfactant combinations of the above types are used to ensure the best dispersion effect and processing performance. For example: Nonionic surfactants (such as TWEEN 80) can be used to promote uniform distribution of plasticizers and other additives, especially when immiscible ingredients are involved.

[0030] Anionic surfactants (such as SDBS) can help stabilize particulate matter in the system and prevent precipitation and stratification.

[0031] Silicone surfactants, such as Dow Corning DC-57, can be used to improve the surface smoothness and feel of the final product while increasing hydrophobicity.

[0032] The plasticizer of the present invention increases the flexibility of the material, reduces its brittleness, and makes the material easier to shape and process.

[0033] The selection of plasticizers is crucial to improving the flexibility and processing performance of the material. The following are several specific ingredients suitable for use as plasticizers in the above foaming materials and their functions: Phthalate Plasticizers Ingredient examples: dioctyl phthalate (DOP), dibutyl phthalate (DBP) This type of plasticizer is one of the earliest widely used plasticizers, with good plasticizing efficiency and cost-effectiveness. They can significantly reduce the glass transition temperature of polymers and increase the flexibility and processability of materials. However, due to environmental and health concerns, the application of some phthalate plasticizers is gradually being restricted.

[0034] Terephthalate Plasticizers: Ingredient Example: Dioctyl terephthalate (DOTP); DOTP is a more environmentally friendly option that provides similar performance to DOP but with better migration resistance and low volatility for applications requiring long-term stability.

[0035] Epoxy Plasticizers: Epoxidized soybean oil (ESO), bisphenol A diglycidyl ether (BADGE); Epoxy plasticizers not only provide good plasticizing effects, but also improve the thermal stability and UV resistance of materials. They are often used in applications that require high stability, such as outdoor building materials.

[0036] Citrate Plasticizers: Ingredient examples: acetyl tributyl citrate (ATBC), acetyl triethyl citrate (ATEC); citric acid ester plasticizers are a relatively environmentally friendly type of plasticizers, with good biodegradability and low toxicity, suitable for food packaging, medical supplies and other fields. This type of plasticizer can also give the material good low-temperature flexibility and migration resistance.

[0037] Aliphatic Dicarboxylic Acid Esters: Ingredient examples: dioctyl adipate (DOA), dioctyl sebacate (DOS); these plasticizers have a low migration tendency and high heat resistance, and are suitable for products that need to remain flexible for a long time. They also show good biodegradability and meet environmental standards.

[0038] Polyester Plasticizers: Ingredient examples: Polyadipate (PA), Polysebacate (PS); Polyester plasticizers provide excellent durability and low migration, and are particularly suitable for high-performance and long-life applications. They can also improve the processing fluidity and surface gloss of the material.

[0039] The foaming agent of the present invention generates gas by chemical or physical means to form a cellular structure, thereby reducing the weight of the material and imparting heat insulation and sound insulation properties. The details are as follows: The following are several specific ingredients suitable for use as foaming agents in the above-mentioned foaming materials and their functions: Physical Blowing Agents: Examples of ingredients: Freon (such as HCFC-142b), hydrocarbons (such as pentane, isopentane), carbon dioxide (CO2); physical blowing agents produce gas by volatilizing or expanding during heating to form bubbles. Freon-based blowing agents were once widely used, but are now gradually restricted due to their destructive effects on the ozone layer. Hydrocarbons are a more environmentally friendly choice with good foaming efficiency and cost-effectiveness. Carbon dioxide is a green blowing agent that is suitable for certain types of polymer systems.

[0040] Chemical Blowing Agents: Ingredient examples: barium azodicarbonamide (ADC), sodium bicarbonate (NaHCO3), nitrosamines (such as N,N'-dinitrosopentamethyltetramine, DPT); chemical foaming agents decompose when heated to produce gases (such as nitrogen, carbon dioxide, etc.), which form a cellular structure. Barium azodicarbonate is one of the most commonly used chemical foaming agents, suitable for a variety of polymer systems, and can provide uniform and fine pores. Sodium bicarbonate is often used in food contact materials because it is non-toxic and its decomposition products are carbon dioxide and water.

[0041] Composite Blowing Agents: Ingredient examples: A mixture of physical foaming agents and chemical foaming agents, such as the combination of ADC and carbon dioxide; a composite foaming agent combines the advantages of physical foaming agents and chemical foaming agents to optimize the pore morphology and distribution while controlling the speed and temperature range of the foaming process. This combination can be flexibly adjusted according to specific application requirements to achieve the best foaming effect.

[0042] The fillers of the present invention include but are not limited to calcium carbonate, talc, and silicon dioxide. Fillers (such as calcium carbonate and talc) are mainly used to reduce costs and can also improve certain physical properties, such as hardness and dimensional stability. Without affecting the main functions, the cost-effectiveness ratio is optimized and the comprehensive physical properties of the material are also enhanced.

[0043] The stabilizer of the present invention prevents the material from deteriorating or degrading during processing and use, especially under high temperature conditions. The following are several specific components and their functions suitable for use as stabilizers in the above-mentioned foaming materials: Lead salt stabilizer: Lead stabilizers (such as lead salts, lead soaps); provide excellent thermal stability, but their application is currently strictly limited due to their toxicity issues.

[0044] Calcium-Zinc Stabilizers: Ingredient examples: Calcium zinc stabilizers (such as Ca / Zn composite stabilizers); have good thermal stability and non-toxic properties, suitable for food contact materials and applications with high environmental requirements. They can also provide certain light stability and anti-aging properties.

[0045] Organotin Stabilizers: Ingredient examples: Butyltin stearate, di-n-octyltin maleate; provide excellent thermal stability and transparency, especially suitable for applications requiring high transparency.

[0046] The adhesion promoter of the present invention comprises a silane coupling agent or a titanate compound. The adhesion promoter can significantly increase the bonding strength between the foaming material and other materials or coatings, simplifying the production process. The foaming material can achieve efficient bonding without additional surface treatment, thereby improving the integration and application convenience of the overall system.

[0047] By mixing these components in a specific ratio, the present invention provides a foaming material that is not easy to fall dust and absorb water, and not only has excellent hydrophobicity and dustproof properties, but also has excellent adhesion with other materials or coatings. While maintaining lightweight and excellent physical properties, this material also exhibits excellent processing performance and long life. It is suitable for a wide range of application scenarios, such as building insulation, automotive interiors, packaging materials and other fields, meeting the needs of modern industry for high-performance composite materials. Example 1

[0048] In this embodiment, a foaming material that is not easy to collect dust and absorb water is provided. The foaming material is composed of the following formula components in parts by weight to ensure that the material has hydrophobic and dustproof properties and enhances adhesion with other materials or coatings, including: 30 parts of olefin polymer, 2 parts of modified polysiloxane, 1 part of waterproof modifier, 0.5 parts of antioxidant, 0.5 parts of surfactant, 2 parts of plasticizer, 3 parts of foaming agent, 10 parts of filler, 1 part of stabilizer, and 1 part of adhesion promoter.

[0049] In this embodiment, the preparation method of the above-mentioned foaming material that is not easy to fall dust and not easy to absorb water is as follows: 1. Raw material preparation and pretreatment Olefin polymer: Low-density polyethylene (LDPE) is selected as the base material, with a weight of 30 parts. Before mixing, the LDPE particles are placed in a preheating device and preheated at 80-120°C for 30 minutes to improve fluidity and uniformity during subsequent processing.

[0050] Modified polysiloxane: Use epoxy-modified polydimethylsiloxane, 2 parts by weight. This modified polysiloxane helps to improve surface energy and adhesion performance.

[0051] Waterproof modifier: Perfluoroalkylethanol is used, with a weight portion of 1 part, providing excellent waterproof effect.

[0052] Antioxidant: Irganox 1010 (pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate) was used at a weight of 0.5 parts to prevent oxidative degradation of the material during processing and use.

[0053] Surfactant: Select TWEEN80 (polyoxyethylene sorbitan monooleate), 0.5 parts by weight, to promote uniform dispersion of the ingredients.

[0054] Plasticizer: Use dioctyl terephthalate (DOTP) at 2 parts by weight to increase the flexibility and processability of the material.

[0055] Stabilizer: Use calcium zinc composite stabilizer, 1 part by weight, to ensure the stability of the material at high temperatures.

[0056] Adhesion promoter: Silane coupling agent is used, with 1 part by weight, to enhance the bonding strength with other materials or coatings.

[0057] 2. Preliminary mixing to obtain mixture A The preheated olefin polymer, modified polysiloxane, waterproof modifier, antioxidant, surfactant, plasticizer, stabilizer and adhesion promoter were added into a high-speed mixer and stirred at 600 rpm for 5 minutes at room temperature until all the ingredients were fully mixed to form a mixture A.

[0058] 3. Add foaming agent and mix to obtain mixture B Foaming agent: select barium azodicarboxylate (ADC), 3 parts by weight.

[0059] Add a foaming agent to mixture A, and control the mixing temperature at 40°C and the mixing pressure at 0.5 MPa. Use a high-speed stirring device, set the stirring speed to 800 rpm, and the stirring time to 3 minutes to ensure that the foaming agent is evenly distributed throughout the mixture. During the entire mixing process, a closed system operation is adopted to prevent the entry of external air and moisture, which may affect the foaming effect, thereby obtaining mixture B.

[0060] 4. Add filler and continue mixing to obtain mixture C Calcium carbonate was added as a filler in the mixture B at a weight of 10 parts, and stirring was continued at 1200 rpm for 3 minutes until all ingredients were fully blended to form the final mixture C.

[0061] 5. Compression molding The mixture C is molded into a foamed material of a desired shape: Molding temperature: set to 150-200℃; Molding pressure: set to 5-15MPa; Holding time: set to 3-10 minutes.

[0062] Ensure that the internal structure of the material is uniform and the surface is flat. After the molding is completed, the molded foam material is immediately cooled and shaped, demolded, and necessary surface treatments are performed as needed, such as plasma treatment or corona treatment, to further improve the surface properties of the material and increase the surface energy, thereby improving the bonding strength with other materials or coatings.

[0063] 6. Post-processing The foamed material is post-processed after molding, including but not limited to dimensional trimming, quality inspection and other steps to ensure that the product meets the specification requirements. Finally, the finished product is packaged and prepared for shipment or further processing.

[0064] Through the above specific embodiments, the entire process from raw material preparation to final product formation is described in detail, ensuring that the foaming material that is not easy to collect dust and absorb water not only has the expected functional properties, but also can form good adhesion with other materials or coatings, while ensuring the consistency of the production process and the reliability of product quality.

[0065] Experimental data In order to evaluate the performance of the foamed material prepared in Example 1, the following tests were performed and the corresponding experimental data were recorded: 1. Hydrophobicity test A contact angle meter is used to measure the contact angle of a water drop on a material surface to evaluate its hydrophobicity.

[0066] Contact angle (°): The average contact angle is 105° Conclusion: The material exhibits good hydrophobicity and it is difficult for water droplets to adhere to its surface.

[0067] 2. Dustproof performance test After the samples were exposed to the dust-containing environment for 72 hours, the amount of dust deposition was observed and quantified using an optical microscope.

[0068] Dust deposition (%): about 40% of the control Conclusion: This material has good dustproof performance and can effectively reduce dust adsorption.

[0069] 3. Adhesion performance test The peel strength between the material and a standard polyurethane coating was determined using a tensile tester.

[0070] Peel strength (N / cm): Average peel strength is 1.2N / cm Conclusion: The material has good adhesion to other materials or coatings and effective bonding can be achieved without additional surface treatment.

[0071] 4. Mechanical properties test Compression strength and tensile strength tests were performed to evaluate the mechanical properties of the material.

[0072] Compression strength (MPa): average compression strength is 0.8MPa Tensile strength (MPa): Average tensile strength is 1.5MPa Conclusion: This material has sufficient mechanical strength and is suitable for a variety of application scenarios.

[0073] 5. Density test Measure the density of foamed materials to assess their lightweight properties.

[0074] Density (g / cm³): average density is 0.06g / cm³ Conclusion: This material has a low density and meets the requirements of lightweight materials.

[0075] It can be seen from the above experimental data that the dust-resistant and water-resistant foaming material prepared in Example 1 exhibits excellent performance in terms of hydrophobicity, dustproof performance, adhesion performance, mechanical properties and density. These results verify the effectiveness of the formula of the present invention, especially the significant improvements brought about by the introduction of modified polysiloxane, waterproof modifier and adhesion promoter. This technical solution not only simplifies the production process and reduces production costs, but also ensures the high performance of the material, meeting the needs of modern industry for high-performance composite materials. Example 2

[0076] In this embodiment, a foaming material that is not easy to collect dust and absorb water is provided. The foaming material is composed of the following formula components in parts by weight to ensure that the material has hydrophobic and dustproof properties and enhances adhesion with other materials or coatings, including: 40 parts of olefin polymer, 5 parts of modified polysiloxane, 3 parts of waterproof modifier, 1 part of antioxidant, 2 parts of surfactant, 6 parts of plasticizer, 5 parts of foaming agent, 20 parts of filler, 3 parts of stabilizer, and 3 parts of adhesion promoter.

[0077] In this embodiment, the preparation method of the above-mentioned foaming material that is not easy to fall dust and not easy to absorb water is as follows: 1. Raw material preparation and pretreatment Olefin polymer: High-density polyethylene (HDPE) is selected as the base material, with a weight of 40 parts. Before mixing, the HDPE particles are placed in a preheating device and preheated at 80-120°C for 30 minutes to improve fluidity and uniformity during subsequent processing.

[0078] Modified polysiloxane: 5 parts by weight of epoxy-modified polydimethylsiloxane is used. This modified polysiloxane helps to improve surface energy and adhesion performance.

[0079] Waterproof modifier: 3 parts by weight of perfluoroalkylethanol modified with silk fibroin is used to provide excellent waterproof effect.

[0080] Antioxidant: Use Irganox 1076 (β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate) at 1 part by weight to prevent oxidative degradation of the material during processing and use.

[0081] Surfactant: Select TWEEN80 (polyoxyethylene sorbitan monooleate), 2 parts by weight, to promote uniform dispersion of the ingredients.

[0082] Plasticizer: Dioctyl terephthalate (DOTP) is used at 6 parts by weight to increase the flexibility and processability of the material.

[0083] Stabilizer: Use calcium zinc composite stabilizer, 3 parts by weight, to ensure the stability of the material at high temperatures.

[0084] Adhesion promoter: Silane coupling agent is used, 3 parts by weight, to enhance the bonding strength with other materials or coatings.

[0085] 2. Preliminary mixing to obtain mixture A The preheated olefin polymer, modified polysiloxane, waterproof modifier, antioxidant, surfactant, plasticizer, stabilizer and adhesion promoter were added into a high-speed mixer and stirred at 600 rpm for 5 minutes at room temperature until all the ingredients were fully mixed to form a mixture A.

[0086] 3. Add foaming agent and mix to obtain mixture B Foaming agent: barium azodicarboxylate (ADC) is selected, with a weight portion of 5 parts.

[0087] Add a foaming agent to mixture A, and control the mixing temperature at 60°C and the mixing pressure at 1.0 MPa. Use a high-speed stirring device, set the stirring speed to 1200 rpm, and the stirring time to 5 minutes to ensure that the foaming agent is evenly distributed throughout the mixture. During the entire mixing process, a closed system operation is adopted to prevent the entry of external air and moisture, which affects the foaming effect, thereby obtaining mixture B.

[0088] 4. Add filler and continue mixing to obtain mixture C Calcium carbonate was added as a filler in the amount of 20 parts by weight to the mixture B, and the mixture was stirred at a speed of 1200 rpm for 3 minutes until all the ingredients were fully blended to form the final mixture C.

[0089] 5. Extrusion molding The mixture C is extruded through a twin-screw extruder: Extrusion temperature: set to 180-200℃, with segmented temperature control to ensure uniform heating of the material.

[0090] Screw speed: set to 40-60 rpm to ensure that the material is fully plasticized and foamed.

[0091] Mold temperature: set to 40-60℃ to facilitate the expansion of foaming gas and the formation of pore structure.

[0092] Cooling method: Use water-cooling shaping device to quickly cool and shape to prevent bubble collapse.

[0093] After being extruded through the extruder, the material is made into the desired continuous shape (such as sheets, tubes, etc.), and is cut or trimmed to the specified length or size after cooling and shaping.

[0094] 6. Surface treatment The foamed material after extrusion molding is subjected to necessary surface treatment, such as plasma treatment or corona treatment, to further improve the surface properties of the material and increase the surface energy, thereby improving the bonding strength with other materials or coatings.

[0095] 7. Post-processing The foamed material is post-processed after molding, including but not limited to dimensional trimming, quality inspection and other steps to ensure that the product meets the specification requirements. Finally, the finished product is packaged and prepared for shipment or further processing.

[0096] Test methods and results 1. Hydrophobicity test A contact angle meter is used to measure the contact angle of a water drop on a material surface to evaluate its hydrophobicity.

[0097] The average contact angle is 115°.

[0098] Conclusion: The foamed material of the present invention exhibits better hydrophobicity, and it is more difficult for water droplets to adhere to its surface.

[0099] 2. Dustproof performance test After the samples were exposed to the dust-containing environment for 72 hours, the amount of dust deposition was observed and quantified using an optical microscope.

[0100] The amount of dust deposited is significantly reduced, about 30% of the control.

[0101] Conclusion: The foam material of the present invention has better dustproof performance and can effectively reduce the adsorption of dust.

[0102] 3. Adhesion performance test The peel strength between the material and a standard polyurethane coating was determined using a tensile tester.

[0103] The average peel strength is 1.5N / cm Conclusion: The adhesion performance between the foamed material of the present invention and other materials or coatings is significantly enhanced, and good bonding effect can be achieved without additional surface treatment.

[0104] 4. Mechanical properties test Compression strength and tensile strength tests were performed to evaluate the mechanical properties of the material.

[0105] Compression strength (MPa): average compression strength is 0.9MPa Tensile strength (MPa): Average tensile strength is 1.6MPa Conclusion: This material has sufficient mechanical strength and is suitable for a variety of application scenarios.

[0106] 5. Density test Measure the density of foamed materials to assess their lightweight properties.

[0107] Density (g / cm³): average density is 0.07g / cm³ Conclusion: This material has a low density and meets the requirements of lightweight materials.

[0108] It can be seen from the above experimental data that the dust-resistant and water-resistant foaming material prepared in Example 2 exhibits excellent performance in terms of hydrophobicity, dustproof performance, adhesion performance, mechanical properties and density. These results verify the effectiveness of the formula of the present invention, especially the significant improvements brought about by the introduction of modified polysiloxane, waterproof modifier and adhesion promoter. This technical solution not only simplifies the production process and reduces production costs, but also ensures the high performance of the material, meeting the needs of modern industry for high-performance composite materials. Example 3

[0109] In this embodiment, a foaming material that is not easy to collect dust and absorb water is provided. The foaming material is composed of the following formula components in parts by weight to ensure that the material has hydrophobic and dustproof properties and enhances adhesion with other materials or coatings, including: 50 parts of olefin polymer, 8 parts of modified polysiloxane, 5 parts of waterproof modifier, 2 parts of antioxidant, 3 parts of surfactant, 10 parts of plasticizer, 7 parts of foaming agent, 30 parts of filler, 4 parts of stabilizer, and 6 parts of adhesion promoter.

[0110] In this embodiment, the preparation method of the above-mentioned foaming material that is not easy to fall dust and not easy to absorb water is as follows: 1. Raw material preparation and pretreatment Olefin polymer: Linear low-density polyethylene (LLDPE) was selected as the base material, with a weight of 50 parts. Before mixing, the LLDPE particles were placed in a preheating device and preheated at 80-120°C for 30 minutes to improve fluidity and uniformity during subsequent processing.

[0111] Modified polysiloxane: 8 parts by weight of epoxy-modified polydimethylsiloxane is used. This modified polysiloxane helps to improve surface energy and adhesion performance.

[0112] Waterproof modifier: 5 parts by weight of perfluoroalkylethanol modified with silk fibroin is used to provide excellent waterproof effect.

[0113] Antioxidant: Irganox 1010 (pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate) was used at 2 parts by weight to prevent oxidative degradation of the material during processing and use.

[0114] Surfactant: Select TWEEN80 (polyoxyethylene sorbitan monooleate), 3 parts by weight, to promote uniform dispersion of the ingredients.

[0115] Plasticizer: Dioctyl terephthalate (DOTP) is used at 10 parts by weight to increase the flexibility and processability of the material.

[0116] Stabilizer: Use calcium zinc composite stabilizer, 4 parts by weight, to ensure the stability of the material at high temperatures.

[0117] Adhesion promoter: Silane coupling agent is used, with 6 parts by weight, to enhance the bonding strength with other materials or coatings.

[0118] 2. Preliminary mixing to obtain mixture A The preheated olefin polymer, modified polysiloxane, waterproof modifier, antioxidant, surfactant, plasticizer, stabilizer and adhesion promoter were added into a high-speed mixer and stirred at 600 rpm for 5 minutes at room temperature until all the ingredients were fully mixed to form a mixture A.

[0119] 3. Add foaming agent and mix to obtain mixture B Blowing agent: barium azodicarboxylate (ADC) is selected, with a weight portion of 7 parts.

[0120] Add a foaming agent to mixture A, and control the mixing temperature at 80°C and the mixing pressure at 2.0 MPa. Use a high-speed stirring device, set the stirring speed to 1500 rpm, and the stirring time to 8 minutes to ensure that the foaming agent is evenly distributed throughout the mixture. During the entire mixing process, a closed system operation is adopted to prevent the entry of external air and moisture, which affects the foaming effect, thereby obtaining mixture B.

[0121] 4. Add filler and continue mixing to obtain mixture C Calcium carbonate was added as a filler in the amount of 30 parts by weight to the mixture B, and stirring was continued at 1200 rpm for 3 minutes until all ingredients were fully blended to form the final mixture C.

[0122] 5. Injection molding The mixture C is molded by injection molding machine: Injection temperature: set to 170-200℃, with segmented temperature control to ensure uniform heating of the material.

[0123] Mold temperature: set to 40-60℃ to facilitate the expansion of foaming gas and the formation of pore structure.

[0124] Injection pressure: set to 80-120MPa to ensure that the material can fully fill the mold cavity.

[0125] Holding time: set to 5-10 seconds to ensure that the material is completely solidified in the mold and forms a stable cellular structure.

[0126] Cooling method: Use water cooling or air cooling setting device to quickly cool and set the shape to prevent bubble collapse.

[0127] Through the injection molding machine, the material is injected into the preheated mold to form the required complex shape (such as automotive interior parts, home appliance housings, etc.). After cooling and shaping, the mold is removed and the product size accuracy and appearance quality are inspected.

[0128] 6. Surface treatment The foamed material after injection molding is subjected to necessary surface treatment, such as plasma treatment or corona treatment, to further improve the surface properties of the material and increase the surface energy, thereby improving the bonding strength with other materials or coatings.

[0129] 7. Post-processing The foamed material is post-processed after molding, including but not limited to dimensional trimming, quality inspection and other steps to ensure that the product meets the specification requirements. Finally, the finished product is packaged and prepared for shipment or further processing.

[0130] Experimental data In order to evaluate the performance of the foamed material prepared in Example 3, the following tests were performed and the corresponding experimental data were recorded: 1. Hydrophobicity test A contact angle meter is used to measure the contact angle of a water drop on a material surface to evaluate its hydrophobicity.

[0131] Contact angle (°): The average contact angle is 120° Conclusion: The material exhibits very excellent hydrophobicity and water droplets hardly adhere to its surface.

[0132] 2. Dustproof performance test After the samples were exposed to the dust-containing environment for 72 hours, the amount of dust deposition was observed and quantified using an optical microscope.

[0133] Dust deposition (%): about 20% of the control Conclusion: This material has excellent dust-proof performance and can significantly reduce dust absorption.

[0134] 3. Adhesion performance test The peel strength between the material and a standard polyurethane coating was determined using a tensile tester.

[0135] Peel strength (N / cm): Average peel strength is 1.8N / cm Conclusion: The material has very strong adhesion to other materials or coatings and no additional surface treatment is required to achieve efficient bonding.

[0136] 4. Mechanical properties test Compression strength and tensile strength tests were performed to evaluate the mechanical properties of the material.

[0137] Compression strength (MPa): average compression strength is 1.2MPa Tensile strength (MPa): Average tensile strength is 2.0MPa Conclusion: This material has high mechanical strength and is suitable for application scenarios requiring good mechanical properties.

[0138] 5. Density test Measure the density of foamed materials to assess their lightweight properties.

[0139] Density (g / cm³): average density is 0.05g / cm³ Conclusion: This material has a low density and meets the requirements of lightweight materials.

[0140] 6. Thermal stability test The thermal stability of the material was tested by thermogravimetric analysis (TGA) to evaluate its performance in high temperature environments.

[0141] Initial decomposition temperature (℃): >280℃ Conclusion: The material exhibits good thermal stability and can maintain structural integrity at higher temperatures.

[0142] It can be seen from the above experimental data that the non-dusting and non-water-absorbing foaming material prepared in Example 3 exhibits excellent performance in terms of hydrophobicity, dustproof performance, adhesion performance, mechanical properties, density and thermal stability. These results verify the effectiveness of the formula of the present invention, especially the significant improvements brought about by the introduction of modified polysiloxane, waterproof modifier and adhesion promoter. This technical solution not only simplifies the production process and reduces production costs, but also ensures the high performance of the material and meets the needs of modern industry for high-performance composite materials. This material is particularly suitable for use in the fields of building insulation, automotive interiors, packaging materials, etc., providing better functional characteristics and application convenience.

[0143] In order to verify the superiority of the foam material provided by the present invention in terms of hydrophobicity, dustproof performance and adhesion with other materials or coatings, we designed a comparative experiment. The experiment used a traditional foam material as a control group and compared the performance of the two through a series of tests.

[0144] Comparative Example: This comparative example is different from Example 2 in that modified polysiloxane, waterproof modifier and adhesion promoter are not used.

[0145] Olefin polymer: High-density polyethylene (HDPE), 40 parts Modified polysiloxane: epoxy-modified polydimethylsiloxane, 0 parts Waterproofing modifier: Silk fibroin-modified perfluoroalkylethanol, 0 parts Antioxidant: Irganox 1076, 1 part Surfactant: TWEEN80, 2 parts Plasticizer: Dioctyl terephthalate (DOTP), 6 parts Stabilizer: calcium zinc composite stabilizer, 3 parts Adhesion promoter: silane coupling agent, 0 parts Blowing agent: barium azodicarboxylate (ADC), 5 parts Filler: Calcium carbonate, 20 parts Test methods and results 1. Hydrophobicity test A contact angle meter is used to measure the contact angle of a water drop on a material surface to evaluate its hydrophobicity.

[0146] Comparative example: average contact angle is 90° Conclusion: The foaming materials of Examples 1-3 of the present invention exhibit better hydrophobicity, and water droplets are more difficult to adhere to their surfaces.

[0147] 2. Dustproof performance test After the samples were exposed to the dust-containing environment for 72 hours, the amount of dust deposition was observed and quantified using an optical microscope.

[0148] Comparative example: higher dust deposition Conclusion: The foaming materials of Examples 1-3 of the present invention have better dustproof performance and can effectively reduce the adsorption of dust.

[0149] 3. Adhesion performance test The peel strength between the material and a standard polyurethane coating was determined using a tensile tester.

[0150] Comparative example: average peel strength is 0.5N / cm Conclusion: The adhesion performance between the foaming materials of Examples 1-3 of the present invention and other materials or coatings is significantly enhanced, and good bonding effects can be achieved without additional surface treatment.

[0151] Through comparative experiments, it can be seen that the dust-resistant and water-resistant foaming material provided by the present invention is superior to traditional foaming materials in terms of hydrophobicity, dustproof performance and adhesion performance. This is mainly due to the modified polysiloxane, waterproof modifier, antioxidant, surfactant, plasticizer, stabilizer and adhesion promoter introduced in the formula. These ingredients work synergistically to significantly improve the overall performance of the material. This technical solution not only simplifies the production process and reduces production costs, but also ensures the high performance of the material, meeting the needs of modern industry for high-performance composite materials.

[0152] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions described in the aforementioned embodiments or to make equivalent substitutions for some of the technical features therein. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A foaming material that is not easy to fall dust or absorb water, characterized in that: The foaming material is composed of the following formula ingredients in parts by weight, including: 30-50 parts of olefin polymer; 2-8 parts of modified polysiloxane; 1-5 parts of waterproof modifier; 0.5-2 parts of antioxidant; Surfactant 0.5-3 parts; 2-10 parts of plasticizer; 3-7 parts of foaming agent; 10-30 parts of filler; 1-4 parts of stabilizer; Adhesion promoter 1-6 parts.

2. The foaming material that is not easy to fall dust or absorb water according to claim 1, characterized in that: The olefin polymer is selected from one or more combinations of low-density polyethylene, linear low-density polyethylene, and high-density polyethylene.

3. The foaming material that is not easy to fall dust or absorb water according to claim 1, characterized in that: The modified polysiloxane is polydimethylsiloxane modified by amino, epoxy or other functional groups.

4. The foaming material that is not easy to fall dust or absorb water according to claim 1, characterized in that: The waterproof modifier is perfluoroalkylethanol.

5. The foaming material that is not easy to fall dust or absorb water according to claim 1, characterized in that: The waterproof modifier is perfluoroalkylethanol modified with silk fibroin.

6. The foaming material that is not easy to fall dust or absorb water according to claim 1, characterized in that: The adhesion promoter includes a silane coupling agent or a titanate compound.

7. A method for preparing a foamed material as claimed in any one of claims 1 to 6, characterized in that: The following steps are involved: 30-50 parts of olefin polymer, 2-8 parts of modified polysiloxane, 1-5 parts of waterproof modifier, 0.5-2 parts of antioxidant, 0.5-3 parts of surfactant, 2-10 parts of plasticizer, 1-4 parts of stabilizer and 1-6 parts of adhesion promoter are uniformly mixed to obtain mixture A; Adding 3-7 parts of a foaming agent to the mixture, and fully mixing the mixture under controlled temperature and pressure conditions to obtain a mixture B; Add 10-30 parts of filler to mixture B and continue stirring until all ingredients are completely blended to obtain mixture C; The mixture C is made into a foam material of a desired shape through extrusion, injection or compression molding, and the molded foam material is cooled, shaped, demolded and surface treated.

8. The method according to claim 7, characterized in that The olefin polymer is preheated before mixing, and the preheating temperature ranges from 80 to 120°C.

9. The method according to claim 7, characterized in that: The molding process adopts compression molding, the molding temperature is 150-200°C, the molding pressure is 5-15MPa, and the holding time is 3-10 minutes.

10. The method according to claim 7, characterized in that The mixture is mixed thoroughly under controlled temperature and pressure conditions to obtain a mixture B, comprising: The temperature is controlled at 40-80°C and the mixing pressure is maintained at 0.5-2.0MPa; A high-speed stirring device is used with the stirring speed set at 800-1500 rpm and the stirring time set at 3-8 minutes to obtain a mixture B.